EFFECTS OF ENVIRONMENTAL FACTORS ON GROWTH AND SURVIVAL AND CERTAIN REPRODUCTIVE TRAITS OF HAIR GOATS - K. Alkoyak; I. Güngör (Journal of Animal and Plant Sciences, 2022)
The present study was carried out to determine the growth and survival rate, the environmental factors affecting these characteristics and the reproductive characteristics of Hair goats raised under farm conditions in the province of Adıyaman, Turkey, for the first time in the region, from birth to weaning (90 days). The birth weight data of 13,751 kids born to Hair goats raised in 48 different enterprises between 2016–2018 was acquired, and the weaning weight data of 12,855 kids were used in the study. As a general average over three years, the birth weight, 60-day live weight, weaning weight and daily live weight gain (DLWG) of the kids were 2.80±0.007, 11.34±0.041, 15.59±0.062 kg and 141.72±0.690 g, respectively. Among the environmental factors examined related to these characteristics, the effects of the dam's age, the enterprise, the year of birth, the gender and the birth type were found to be statistically significant (p<0.05, p<0.01, p<0.001). The average survival rate of kids in weaning was 93.48%. Aside from gender, the effect of the dam's age, year of birth and birth type on the survival rate was determined to be significant (p<0.001). In the study, litter size and twin birth rates were generally 1.10 and 8.71%, respectively. The results of this research, based on the above data, revealed Hair goat breeding to be sustainable and successful in the region.
Keywords: Hair goat; growth; environmental factors; reproductive characteristics; survival rate